Optimization of bamboo mesoparticle/nylon 6 composite mechanical properties using a response surface methodology - Salih A.A.; Zulkifli R.; Azhari C.H. (Carl Hanser Verlag, 2024)
Indexed by WOS/Scopus/ERA